Bilinear Pairing Based Encryption for Sensor Network - Emerole, Kelechi; Anyaehie, Maurice; Nwadike, Stanley (International Journal of Computer (IJC), 2019)
In this letter, we review some research efforts in the area of Pairing based encryption for data transmission and storage taking note of the computational overhead and consequently present a simple encryption scheme to buttress our initiative further.